Clinical Validation of an Office-Based 14C-UBT (Heliprobe) for H. pylori Diagnosis in Iranian Dyspeptic Patients - Fariborz Mansour-Ghanaei; Omid Sanaei; Farahnaz Joukar (Gastroenterology Research and Practice)
Background. We encountered repeatedly, in our clinical practice, discordant results between UBT and histopathology about H. pylori infection. Goal. To study the diagnostic accuracy of Heliprobe 14C-urea breath test (14C-UBT) for detection of H. pylori infection in an Iranian population. Study. We enrolled 125 dyspeptic patients in our study. All of them underwent gastroscopy, and four gastric biopsies (three from the antrum and one from the corpus) were obtained. One of the antral biopsies was utilized for a rapid urease test (RUT), and three others were evaluated under microscopic examination. Sera from all patients were investigated for the presence of H. pylori IgG antibodies. The 14C-UBT was performed on all subjects using Heliprobe kit, and results were analyzed against the following gold standard (GS): H. pylori infection considered positive when any two of three diagnostic methods (histopathology, RUT, serology) are positive. Results. According to data analysis, the Heliprobe 14C-UBT had 94% sensitivity, 100% specificity, 93% negative predictive value (NPV), 100% positive predictive value (PPV), and 97% accuracy, compared with GS. Conclusion. The Heliprobe 14C-UBT is an easy-to-perform, rapid-response, and accurate test for H. pylori diagnosis, suitable for office use.